A mini-review: phosphodiesterases in charge to balance intracellular cAMP during T-cell activation - Bielenberg, Marie; Kurelic, Roberta; Frantz, Stefan; Nikolaev, Viacheslav O. (Frontiers in Immunology, 2024)
T-cell activation is a pivotal process of the adaptive immune response with 3′,5′-cyclic adenosine monophosphate (cAMP) as a key regulator of T-cell activation and function. It governs crucial control over T-cell differentiation and production of pro-inflammatory cytokines, such as IFN-g. Intriguingly, levels of intracellular cAMP differ between regulatory (Treg) and conventional T-cells (Tcon). During cell-cell contact, cAMP is transferred via gap junctions between these T-cell subsets to mediate the immunosuppressive function of Treg. Moreover, the activation of T-cells via CD3 and CD28 co-stimulation leads to a transient upregulation of cAMP. Elevated intracellular cAMP levels are balanced precisely by phosphodiesterases (PDEs), a family of enzymes that hydrolyze cyclic nucleotides. Various PDEs play distinct roles in regulating cAMP and cyclic guanosine monophosphate (cGMP) in T-cells. Research on PDEs has gained growing interest due to their therapeutic potential to manipulate T-cell responses. So far, PDE4 is the best-described PDE in Tcells and the first PDE that is currently targeted in clinical practice to treat autoimmune diseases. But also, other PDE families harbor additional therapeutic potential. PDE2A is a dual-substrate phosphodiesterase which is selectively upregulated in Tcon upon activation. In this Mini-Review, we hat gelöscht: have been found to 30 hat gelöscht: For instance, 31 hat gelöscht: with the ability to hydrolyze cAMP and cGMP. 32 Recently, it has been shown that PDE2A 33 hat gelöscht: in will highlight the impact of cAMP regulation on T-cell activation and function and summarize recent findings on different PDEs regulating intracellular cAMP levels in T-cells.